Cervicoplasty in Severe Cervical stenosis: a Challenging Problem - Nath, Jyan Dip; Das, Nilanjana (International Journal of Medical Research and Review, 2014)
18 years old patient presented with pain abdomen, whitish discharge, dyspareunia, dysmenorrhoea and delayed menarche was diagnosed as a case of P0+0 with severe cervical stenosis with left sided pyosalpinx. Abdomino perineal approach was done as the surgical procedure. Left sided salpingectomy done, an uterovaginal anastomosis was created keeping malecot’s catheter as a stent. She had normal menstruation without dysmenorrhoea after the operation. Malicot’s catheter was removed later on. She is now under follow-up. Also we used malicot’s catheter as folley’s catheter may come out.